2019
DOI: 10.1186/s12903-018-0698-9
|View full text |Cite
|
Sign up to set email alerts
|

Dental caries and associated factors in 3 to 5-year-old children in Zhejiang Province, China: an epidemiological survey

Abstract: BackgroundDental caries in preschool children is prevalent worldwide, but data regarding its magnitude and associated factors were not available for preschool children in Zhejiang Province, China. This study examines the dental caries situation and its associated factors in Zhejiang Province.MethodsA total of 1591 children aged 3–5 years and their parents or caregivers were enrolled in this study. The condition of their teeth was assessed by three dental technicians qualified to WHO 2013 criteria. A structured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 34 publications
4
25
1
1
Order By: Relevance
“…What interested us was that the children who were exclusively/predominantly breastfed during the first half year of life had a higher risk of ECC. This finding agrees with the results of earlier studies reporting a significant relation between the duration of breastfeeding and ECC in young Chinese children [ 31 , 32 ], similar to its neighboring province of Zhejiang [ 11 ]. Part of the reason might be that breast milk is more likely to cause caries than other types of milk [ 33 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…What interested us was that the children who were exclusively/predominantly breastfed during the first half year of life had a higher risk of ECC. This finding agrees with the results of earlier studies reporting a significant relation between the duration of breastfeeding and ECC in young Chinese children [ 31 , 32 ], similar to its neighboring province of Zhejiang [ 11 ]. Part of the reason might be that breast milk is more likely to cause caries than other types of milk [ 33 ].…”
Section: Discussionsupporting
confidence: 93%
“…This survey reported high prevalence and severity of ECC among preschool children in Guangdong, Southern China, similar to the finding for East China [ 11 ] and higher than that for Southwest China [ 12 ], higher than the national average [ 13 ], and higher than that 10 years ago [ 4 ]. A multitude of factors are associated with the prevalence and severity.…”
Section: Discussionsupporting
confidence: 80%
“…Province is much higher than that in Japanese (31.1%) 9 and English children (31.7%). 10 Compared with more developed countries such as Japan and England, Zhejiang is slower in terms of oral health promotion and treatment, which falls behind its economic development, 13 analysis showed that the prevalence of ECC increased significantly with age. 13 We believe that this is mainly attributed to the cumulative effect of age throughout life.…”
Section: The Prevalence Of Ecc In Children Aged 3-5 Years In Zhejiangmentioning
confidence: 99%
“…The presence of ECC was determined using the dmft index of the WHO 2013 criteria [10]. Three experienced dentists collected the data at kindergartens.…”
Section: This Study Was Approved By the Stomatological Ethics Committmentioning
confidence: 99%